Institutional dimensions of water resource management in South Africa: socio-cultural perspectives - Marais, Sarshen; Kapfudzaruwa, Farai; Pollard, Derck; Haram, Gro (Department of Environmental and Geographical Science, 2016)
Water is an essential resource in everyday life and if managed properly can help alleviate the day to day struggles that most South Africans face. The transition to democracy in South Africa required a process of law reform that saw old acts abolished to make way for new legislation that encapsulate the principles of equity, sustainability, and efficiency. In terms of the National Water Act (NWA) strategies including the national water resource strategy (NWRS) have been developed to facilitate the proper management of water resources. South Africa has been divided into nineteen water catchment management areas, identified in the strategy, and new water management institutions have been designed to help address the problems of water provision, management, conservation and participation by stakeholders in these processes (DWAF, 2004b). This project seeks to analyse and evaluate these new water management arrangements, especially relating to the water user association (WUA). A key focus will be the role that socio-cultural issues, particularly the role of traditional leadership and cultural and religious practices play in determining water management outcomes.